Pengaruh Variabel Harga dan Citra Perusahaan terhadap Keputusan Pembelian Produk Wingsfood - Ella Anastasya Sinambela; Putri Purnama Sari; Samsul Arifin (Universitas Islam Balitar, 2020)
The business world involving well-known corporations is increasingly showing competition through the sale of its products and efforts to dominate the market. One of the well-known corporations in Indonesia is Wingsfood which already has loyal customers because it trusts the products it produces since entering its market. This study aims to determine the effect of price and company image on purchasing decisions of Wingsfood products in the city of Mojokerto. Samples were taken as many as 143 respondents. The analytical tool used is SPSS 25. The research sampling technique uses random sampling. The questionnaire scale uses a Likert scale. Data consists of primary data taken from questionnaires distributed directly to respondents. The analysis used to examine the effect of price and company image is multiple linear analysis. From the results of data processing the regression equation Y = -2.211 + 0.387 + 0.869X2 is obtained. Research shows several findings, namely (1) price significantly influences the purchasing decisions of Wingsfood products in the city of Mojokerto, (2) company image has a significant effect on purchasing decisions of Wingsfood products in Mojokerto, (3) price and image of the company have a simultaneous effect on product purchasing decisions Wingsfood in koto Mojokerto